Telomere length in patients with unclassifiable interstitial lung disease: a cohort study. Issue 2 (27th August 2020) - Ley, Brett; Liu, Shuo; Elicker, Brett M.; Henry, Travis S.; Vittinghoff, Eric; Golden, Jeffrey A.; Jones, Kirk D.; Wolters, Paul J.
Up to 15% of patients with chronic interstitial lung disease (cILD) will remain clinically unclassifiable ( i.e. unclassifiable ILD, uILD) despite thorough clinical evaluation and multidisciplinary team discussion (MDT) [1, 2]. This diagnostic uncertainty translates into uncertainty in expected prognosis and initial treatment approach ( e.g. immunosuppression versus anti-fibrotic medications) for patients with uILD, and it often precludes enrolment into clinical trials. Peripheral blood telomere length (TL) is a genomic biomarker that has been associated with prognosis and harm from immunosuppression in IPF [3, 4]. TL has recently been associated with idiopathic pulmonary fibrosis (IPF)-like morphologic features ( i.e. features of usual interstitial pneumonia, UIP) and reduced survival in other forms of cILD [5–7]. Whether TL demonstrates similar associations in patients with uILD is unknown, but if so, its clinical measurement could reduce diagnostic and therapeutic uncertainty by determining which patients with uILD will have an IPF-like course. The aim of this study was to determine whether TL is associated with clinical features and outcomes in a cohort of patients with uILD. Peripheral blood telomere length predicts survival in patients with unclassifiable interstitial lung disease https://bit.ly/3e3j0sL